2013
DOI: 10.1093/mnras/sts582
|View full text |Cite
|
Sign up to set email alerts
|

The structure and kinematics of dense gas in NGC 2068

Abstract: We have carried out a survey of the NGC 2068 region in the Orion B molecular cloud using HARP on the JCMT, in the 13 CO and C 18 O (J = 3 -2) and H 13 CO + (J = 4 -3) lines. We used 13 CO to map the outflows in the region, and matched them with previously defined SCUBA cores. We decomposed the C 18 O and H 13 CO + into Gaussian clumps, finding 26 and 8 clumps respectively. The average deconvolved radii of these clumps is 6200 ± 2000 AU and 3600 ± 900 AU for C 18 O and H 13 CO + respectively. We have also calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Mitchell et al (2001) mapped the source using SCUBA and weakly detected an associated outflow in 12 CO 3-2. Walker-Smith et al (2013) also observed patches of red-and blueshifted 13 CO 3-2 emission in the vicinity of this source. Matthews & Wilson (2002), using the SCUBA polarimeter, found the polarization toward the source to be consistent with that of its surroundings.…”
Section: B2 Serpens Main Ec 53 (V371 Serp): Periodic Groupmentioning
confidence: 57%
See 1 more Smart Citation
“…Mitchell et al (2001) mapped the source using SCUBA and weakly detected an associated outflow in 12 CO 3-2. Walker-Smith et al (2013) also observed patches of red-and blueshifted 13 CO 3-2 emission in the vicinity of this source. Matthews & Wilson (2002), using the SCUBA polarimeter, found the polarization toward the source to be consistent with that of its surroundings.…”
Section: B2 Serpens Main Ec 53 (V371 Serp): Periodic Groupmentioning
confidence: 57%
“…The source was observed using the SCUBA polarimeter by Matthews & Wilson (2002), and while polarization was seen along the filament where it is located, no polarization was detected toward the source itself. The authors suggest that this end of the filament may lie in the foreground of the nebula, as do Walker-Smith et al (2013). Kang et al (2015) find a high deuteration ratio (HDCO/ H2CO) for this source, implying that it is probably in the very earliest stage of star formation.…”
Section: B10 Orion Ngc 2068 Hops 373: Curved Groupmentioning
confidence: 73%
“…These processes have been studied from an observational point of view at different spatial scales. At large-scales (~ 1 pc) or clump scales, gravoturbulent fragmentation (or thermal Jeans fragmentation) seems to describe well the observations (e. g., Román-Zúñiga et al 2009,Takahashi et al 2013; Walker-Smith et al 2013; Samal et al 2015; Kainulainen et al 2016; Sharma et al 2016; Hacar et al 2017b), although there are cases where the effects of feedback (Busquet et al 2016), or large-scale collapse (Csengeri et al 2017) seem to be important as well. The term of ‘gravoturbulent fragmentation’ refers to the fragmentation that takes place in a turbulent and self-gravitating cloud.…”
Section: Introductionmentioning
confidence: 67%
“…In simulations with turbulent driving, prestellar cores displayed a higher core-to-core velocity dispersion than protostellar cores, and the reverse was true in simulations with decaying turbulence. Observational evidence for both scenarios exists: while Perseus (Kirk et al 2007) agrees with driven turbulence, Ophiuchus (André et al 2007) and NGC 2068(Walker-Smith et al 2013) agree better with the decaying turbulence scenario.…”
Section: Core Motionsmentioning
confidence: 82%